BEBERAPA ASPEK YANG BERPENGARUH TERHADAP KEPUASAN KERJA DAN KINERJA KARYAWAN PT. PLN (PERSERO) RENGAT - Laura,.S,.SE,.MM, Netty (Jurnal Tepak Manajemen Bisnis, 2015)
Abstract.The research was conducted in PT PLN (Persero) Rengat. The purpose of this research are to know the influence of ability, discipline, and training towards the employeeâs performance with individual test and overall test, and to know the influence of performance toward the employeeâs job satisfaction of PT PLN (Persero) Rengat.The research methods used quantitative and qualitative, and the population in this research are 30 employees. By using a sensus. Data obtained with questionnaires. This research used Two phase Multiple Regression Analysis.The result of research shows that the comittment, discipline, and training have been influence of significant toward the performance. It indicated from the value of Fobs > Ftable at the level of Î± = 5% Fobs= 9,004 > Ftable = 2,48 with probability (p) smaller than 0,05 and determination coefficient value (R2) is 21,2%. It means that 21,2% comittment, discipline, and training toward the job satisfaction. A partially (individual test) shows that the value of comittment 0,801, discipline 1,545, training 4,227. This result indicates that training has most dominant influence on job satisfaction, comittment and discipline have influence on the job satisfaction. Job satisfaction has been influence of significant toward the performance (p<0,05) with tobs =7,205> ttable = 1,66298.Key words: performance and job satisfaction